Meningkatkan Keterampilan Mengungkapkan Monolog Descriptive Lisan Sederhana yang Berterima Menggunakan Sistem ICARE di MTs Muhammadiyah 2 Kalibening Banjarnegara - Nur Muhammad Amin (LPPM IAINU Kebumen, 2022)
The key output of the teaching process is the material provided by the students themselves, therefore it is important to conduct research. The methodology used in this investigation is a class of investigative action. Methods of data collection using interviews, tests, observation, and documentation. Data validation using triangulation. Data analysis methods used in this research include quantitative analysis, especially reduction analysis, presentation, and conclusion or verification analysis. The results of this study indicate that: (1) teaching English uses the ICARE system to teach one continuous monologue that is descriptive in nature and includes four learning objectives: Introduce (Introduce), Connect (Connect), Apply (Apply), Reflect (Reflect), and Expand (Expand). (2) The results of Section I show that there are 16 or 43% of participants who have completed the course and 27 or 67% who have not; the overall participation rate was 68. In Part II,